2019
DOI: 10.1042/bsr20190527
|View full text |Cite
|
Sign up to set email alerts
|

The function of histone acetylation in cervical cancer development

Abstract: Cervical cancer is the fourth most common female cancer in the world. It is well known that cervical cancer is closely related to high-risk human papillomavirus (HPV) infection. However, epigenetics has increasingly been recognized for its role in tumorigenesis. Epigenetics refers to changes in gene expression levels based on non-gene sequence changes, primarily through transcription or translation of genes regulation, thus affecting its function and characteristics. Typical post-translational modifications (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 104 publications
0
18
0
1
Order By: Relevance
“…Thus, the balance between euchromatin and heterochromatin could be tightly regulated by histone acetylation and deacetylation ( 105 , 106 ). Nonetheless, studies showed that histone acetylation/deacetylation status were dysregulated in cancer development ( 107 , 108 ), such as cervical cancer ( 109 ), breast cancer ( 110 ), leukemia ( 108 ), and non-small cell lung cancer ( 111 , 112 ). Like histone acetylation, methylation at the histone tails also regulates gene expression ( 113 , 114 ).…”
Section: Tme Epigenetically Regulates Immune Effector Cell Functionsmentioning
confidence: 99%
“…Thus, the balance between euchromatin and heterochromatin could be tightly regulated by histone acetylation and deacetylation ( 105 , 106 ). Nonetheless, studies showed that histone acetylation/deacetylation status were dysregulated in cancer development ( 107 , 108 ), such as cervical cancer ( 109 ), breast cancer ( 110 ), leukemia ( 108 ), and non-small cell lung cancer ( 111 , 112 ). Like histone acetylation, methylation at the histone tails also regulates gene expression ( 113 , 114 ).…”
Section: Tme Epigenetically Regulates Immune Effector Cell Functionsmentioning
confidence: 99%
“…Histone deacetylases remove acetyl residues and associate with condensed chromatin structures, which, in turn, suppress transcription [162]. Because of its significant role in cancer, HDACs became a potential target for cancer treatment [163].…”
Section: Dna Acetylation In Hpv-associated Cancersmentioning
confidence: 99%
“…Acetylation of lysine residues by HATs leads to transcriptionally active chromatin, whereas HDACs remove acetyl residues, thus marking transcriptionally repressed chromatin [43]. The HPV E6 and E7 oncoproteins promote a replication-competent environment in infected cells in part by modulating the expression and activities of HATs and HDACs [44]. The CREB-binding protein (CBP) and p300 are paralogous transcriptional coactivators with intrinsic HAT activity [45].…”
Section: Histone Acetylationmentioning
confidence: 99%